Methidiumpropyl-EDTA-iron(II) cleavage of ribosomal DNA chromatin from Dictyostelium discoideum. - Parish, R W (1986)
We have used methidiumpropyl-EDTA-iron(II) [MPE.Fe(II)] in parallel with micrococcal nuclease to investigate the chromatin structure of the extrachromosomal palindrome ribosomal RNA genes of Dictyostelium. Confirming our earlier results with micrococcal nuclease (1,2), MPE.Fe(II) digested the coding region of rapidly transcribing rRNA genes as a smear, indicating the absence or severe disruption of nucleosomes, whereas in slowly transcribing rRNA genes, a nucleosomal ladder was produced. In the central non-transcribed spacer region of the palindrome, MPE.Fe(II) digestion resulted in a normal nucleosomal repeat, whereas micrococcal nuclease gave a complex banding pattern. The difference is attributed to the lower sequence specificity of MPE.Fe(II) compared to micrococcal nuclease. In the terminal region of the palindrome, however, both substances gave a complex chromatin digestion pattern. In this region the DNA appears to be packaged in structures strongly positioned with respect to the underlying DNA sequence.